The place and role of leisure in the Moscow students’ everyday life in the context of the information society development - Yu. P. Nadekhina; A. A. Kolchin; E. V. Kryukova (Цифровая социология)
The proposed article discusses issues related to the daily life of Moscow students and their leisure, the relevance of which in the context of the development of the information society is associated with increased attention of the state to the educational component of modern educational systems. Moreover, in the conditions of modern realities of the development of the information society, and, consequently, information culture, the format of leisure becomes a significant factor in the socialisation of the individual.   As a goal, the authors of the article identified the analysis of various forms of leisure activities of Moscow students through their questionnaires, which was designed to outline vectors for further research of the place and role of study, family relations and forms of spending free time in a student’s life.   Special attention is paid to modern forms of leisure for students, such as: spending time on the Internet, visiting experimental theaters and cinemas, watching talk shows and entertainment programs, visiting immersive shows, participating in modern youth organisations, etc. Summarising the results of the study, it was concluded that at the moment no more than 20 % of the surveyed Moscow students choose “modern” forms of leisure activities. The conducted research revealed the students’ clear preferences in spending their free time, as well as their value orientations.